Ethics Based on Primacy of Existence (Aṣālat al-Wujūd) with a Focus on Mullā Sadrā's Primacy of Existence - Hossein Atrak; Manouchehr Shaminejad (Journal of Philosophical Investigations, 2023)
This research endeavors to introduce a novel concept in ethics, namely ethics based on the primacy of existence, drawing upon Aṣālat al-wujūd, the theory of the primacy of existence in ontology. Mullā Sadrā's philosophy, which has three basic tenets—the primacy of existence, substantial motion (Ḥarakat-i Juharī), and gradation in existence (Tashkīk-i wujūd)—is the basis for this doctrine. The primacy of existence holds that quiddity is a mental construct and that existence is fundamental. The writers distinguished between two conceptions of ethics in this regard: one based on existence and the other on quiddity. Human quiddity is fixed and does not grade, hence ethics based on quiddity's primacy will always be fixed and the same for every individual. Moral obligations are universal and shared by all individuals. On the other hand, moral obligations for humans might vary depending on their existential status, according to ethics grounded in the primacy of existence. Moral oughts and ought nots are established by human existential grades in this ethics. This ethical model is flexible and dynamic.